EFFECT OF ASCORBIC ACID IN MITIGATING COPPER STRESS IN PEA (PISUM SATIVUM L.) - ABBAS, T; TASADAQ, M; AHMAD, W; YOUNAS, HS; TARIQ, MU; IRFAN, M; ALTAF, K (Biological and Clinical Sciences Research Journal, 2024)
This study investigated the impact of excessive copper concentrations and varying ascorbic acid levels on the growth and yield of pea seedlings (Pisum sativum L.). Pea plants were subjected to 50 μM copper stress and subsequent foliar spray of control (distilled water), 30 mM, and 60 mM ascorbic acid were applied. 'Orion' pea seeds were sown in pots filled with sand. Hoagland's solution was provided as a nutrient source. After 35 days, 50 μM copper sulfate was applied to the soil as a basal dose. A week later, ascorbic acid at 0, 30, and 60 mM concentrations was applied as a foliar spray. The experiment was conducted in a completely randomized design with six treatments and three replications. Results showed that ascorbic acid significantly improved plant growth as evidenced by increased fresh and dry weight, shoot length, leaf area, and chlorophyll content. The combination of 60 mM ascorbic acid with 50 μM copper resulted in the highest values for most growth parameters, including yield components such as the number of pods and seeds. These findings suggested that ascorbic acid can effectively mitigate the negative effects of copper stress on pea plants, promoting growth, enhancing photosynthetic efficiency, and ultimately leading to increased yield. Copper, an essential micronutrient, can become toxic at high concentrations, while ascorbic acid plays a crucial role in modulating plant growth and stress tolerance.